Investigating low cost hole transporting materials for perovskite solar cells - Liu, J (2016)
Organic-inorganic halide perovskites (CH3NH3PbI3) have attracted strong attention of photovoltaic research community since 2012, benefiting from the low cost of organolmetal halide perovskite precursors and their simple solution processability. However, the chemical instability of this material, especially in high humidity environment, restricts its photovoltaic application in industry. This thesis is focusing on employing novel hole transporting materials (HTMs) for perovskite solar cells (PSCs). Besides their main responsibility acting as a hole selective layer increasing the photovoltaic performance, HTMs can also play an additional role serving as moisture blocking layers, enhancing the stability of PSCs. Chapter 2 presents the general background knowledge of the physics of solar cells, delving deeper into the working principle of PSCs and related researches about the HTMs and stability of the devices. In chapter 3, the device fabrication techniques and the characterization methods used are presented in details. Commencing from chapter 4, the application of two kinds of HTMs and related studies are discussed. Chapter 4 demonstrates the use of a p-type organic material, PEDOT, on 'regular' structured PSCs, achieving devices with decent power conversion efficiency (PCE) but relatively huge hysteresis and low stabilized power output (SPO). Stability analysis shows this organic material provides a better protection of the perovskite film comparing to that of doped Spiro-OMeTAD, which is the most generally used HTM. Chapter 5 presents a study about CuSCN, an inorganic p-type semiconductor, being applied in PSCs as HTM. The CuSCN based devices show comparable performance to that of Spiro-OMeTAD based devices, but an interfacial degradation mechanism is found to facilitate the perovskite degradation even in inert atmosphere. A facile sealing protocol is established to deal with this problem, leading to super stable photovoltaic devices under thermal stressing. The following chapter 6 demonstrates a CuI doping technique to improve the hole transporting effectiveness of CuSCN layer. This doping technique modifies the morphology of CuSCN film and leads to a substantial improvement in the photovoltaic performance.